Electronic properties of free-standing TiO2 nanotube arrays fabricated by electrochemical anodization. Issue 34 (14th September 2015) - Chen, Chi Liang; Dong, Chung-Li; Chen, Chia-Hao; Wu, Jen-Wei; Lu, Ying-Rui; Lin, Chin-Jung; Ya Hsuan Liou, Sofia; Tseng, Chuan-Ming; Kumar, Krishna; Wei, Da-Hua; Guo, Jinghua; Chou, Wu-Ching; et al.
<x xml:space="preserve">Abstract</x> Different electronic structures between the top and bottom of TiNT revealed by XAS, SPEM, and RIXS.